PENGARUH PELATIHAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. ASURANSI JIWASRAYA (PERSERO) KANTOR WILAYAH PEKANBARU - Siregar, Lambok R; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The purpose of the study is to determine the effect of early training work motivation on employee performance in PT. Asuransi Jiwasraya (Persero) Regional Office Pekanbaru. The research data in the form of primary data and secondary data, with the questionnaire as a research instrument.Analysis of the data used by using SPSS.Results of analysis using multiple linear regression, t-test, and the test of determination (R2), and the F-test. The results showed that the training and work motivation simultam significant influence on employee performance. It can be seen from the F-count = 52.867> F-table = 3.18. So that the figures obtained R2 (R Square) of 0.670 or 67%. This shows that the percentage contribution of independent variables (training and motivation) on the dependent variable (performance of employees) by 67% and strong relationships with major award is 0.67. While the remaining percentage of 33% (100% - 67%) is influenced by other variables not included in this study variables.Keywords: Training, Work Motivation, Employee Performance